Relación entre la perfección y la belleza artística en la teoría estética de Alexander Gottlieb Baumgarten e Immanuel Kant - Diez, Renzo (Pontificia Universidad Católica del Perú. Instituto Riva-Agüero, 2022)
This article studies how the role of the concept of perfection in the elucidation of the concept of artistic beauty differs between Baumgarten’s and Kant’s aesthetic doctrine. For both, this beauty is linked to the purpose of the artistic object and the degree to which its configuration is arranged for said purpose determines its perfection. However, the philosophers draw conflicting conclusions from this: in Baumgarten the apprehension of this perfection in sensible discourse is artistic beauty, while in Kant the judgment of artistic beauty is influenced by the consideration of the perfection of the object, but perfection does not determine artistic beauty.

El presente artículo estudia cómo se diferencia el rol del concepto de perfección en la elucidación del concepto de belleza artística entre la doctrina estética de Baumgarten y la de Kant. Para ambos esta belleza está vinculada al fin del objeto artístico y el grado en que su configuración se arregla a dicho fin determina su perfección. Empero, de esto los filósofos extraen conclusiones conflictivas: en Baumgarten la aprehensión de esta perfección en el discurso sensible es belleza artística, mientras que en Kant el juicio de belleza artística es influido por la consideración de la perfección del objeto, pero la perfección no determina la belleza artística.
Keywords: Perfection; Artistic beauty; Consensus phaenomenon; Teleology; Judgement of taste; Perfección; Belleza artística; Consensus phaenomenon; Teleología; Juicio de gusto; https://purl.org/pe-repo/ocde/ford#6.03.01